Improving Early Mathematics Skills Through Contextual Theme-Based Smart Box Media in Early Childhood - Yuliani Waladani; Purwaningsih Purwaningsih; Uswatun Khasanah; Ismatul Khasanah; Ika Sukesmi (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This classroom action research aims to improve early mathematics skills of Group B children at TK Desa Majasto 02 through the implementation of a contextual theme-based "Animals as God's Creatures" smart box media. The primary issue in this study is the children's low ability to comprehend number concepts, simple arithmetic operations (addition and subtraction), and match numbers with the corresponding quantity of objects. The research subjects consisted of 10 children (6 boys and 4 girls). The study was conducted in two cycles, with each cycle comprising planning, acting, observing, and reflecting stages. Data collection techniques employed structured observation and documentation, while data analysis was performed using descriptive comparative analysis. The results indicated a significant improvement in the children's mathematics skills. In the pre-cycle condition, the classical completeness of children's mathematics skills reached only 20% (2 children). Following the intervention in Cycle I, the completeness percentage rose to 50% (5 children) and achieved optimal success in Cycle II at 90% (9 children). These findings prove that utilizing concrete and manipulative smart box media can facilitate the transformation of abstract concepts into concrete understanding, as well as enhance children's active engagement in early mathematics learning